Intrapancreatic Accessory Spleen: A Single Center Experience and A Literature Review - Yu.A., Stepanova; D.A., Ionkin; M.Z., Alimurzaeva; A.V., Glotov; E.A, Akhtanin (Archives of Clinical and Medical Case Reports, 2025)
An accessory spleen (splenuncle) is an extrasplenic accumulation of splenic tissue that has its own blood supply, innervation, capsule, and serous membrane. Although an accessory spleen is not an unusual phenomenon, intrapancreatic localization of such masses is rare. Currently, 247 cases of accessory spleen in the structure of the pancreas have been published in Pubmed database since 2000 (for 25 years). During the period 2012-2024, 3 patients with intrapancreatic accessory spleen (IAS) were identified at A.V. Vishnevsky National Medical Research Center of Surgery (1 man and 2 women aged 38 to 61 years). The presented clinical cases demonstrate the difficulties of ectopic pancreatic spleen differential diagnosis. Despite the obviousness of the radiology picture similar to the visualization of the orthotopic spleen, a similar picture is also characteristic for such focal lesions, as NETs, solid pseudopapillary tumor and kidney cancer metastasis. Nevertheless, a thorough analysis of ultrasound, MSCT and MRI data of the detected lesion using appropriate visualization methods can confirm the diagnosis of IAS without invasive procedures or surgery. This is extremely important for the patient, since the accessory spleen is essentially a benign mass and surgery is not required in the vast majority of cases. Focal lesions can develop in IAS, as in the orthotopic spleen. Currently, Pubmed database contains 66 such lesions, which is 26.4% of all cases of such ectopia (N = 250, also taking into account our 3 cases). Thus, IAS is a diagnosis that should be kept in mind as a differential diagnosis when considering a case with a focal lesion, since this will avoid unnecessary intervention due to erroneous diagnosis.